A STRATEGI PERKEMBANGAN USAHA RUMAH AMPLANG “BAROKAH” KELURAHAN LOK TUAN KECAMATAN BONTANG UTARA: STRATEGI PENGEMBANGAN USAHA - SINTYA NURUL KURNIAWATI; Said Abdusysyahid; Eko Sugiharto (2339-1324, 2023)
ABSTRACT SINTYA NURUL KURNIAWATI, 2022.Strategy for Development of Amplang “Barokah” House in Lok Tuan Village, North Bontang District (Supervised by Said Abdusysyahid and Eko Sugiharto). The purpose of this study was to find out how the Amplang ”Barokah” House Business Development Strategy, Lok Tuan Village, Bontang Utara District. This research was carried out from January 2021 to March 2022 in Lok Tuan Village, North Bontang District. A sample of 10 respondents with reference to predetermined questions in the form of a questionnaire. The results showed that the results of IFAS and EFAS, it can be seen that the total value for IFAS is 0.845 and for EFAS is 0.258. In the SWOT matrix, several alternative strategies are obtained by using strengths to take advantage of opportunities and using strengths to avoid threats. In the SWOT analysis diagram, it is known that the Amplang “Barokah” House Business is located in quadrant I, meaning this is a situation that this business has strengths and opportunities, although on the other hand this business faces several obstacles and weaknesses. The strategy that must be applied in this condition is the Growth Strategy or growth strategy.